Pengendalian Persediaan Fruktosa Di PT. API - Enjang Kartiwa Nugraha; Rahmat Saputra (Journal Industrial Manufacturing, 2024)
This journal discusses the analysis of fructose inventory control at PT. API. The aim of this research is to optimize fructose supplies at PT. API by using appropriate inventory control methods. The data used in this research is data on daily fructose consumption at PT. API during the period May 2023 to May 2024. The methods used in this research are descriptive analysis and statistical analysis. Descriptive analysis is used to describe fructose consumption data, while statistical analysis is used to determine appropriate inventory control methods. The research results show that the fructose supply at PT. The API is not well controlled. This is indicated by high fluctuations in fructose use and suboptimal supply levels. Keywords: Fruktose, Inventory control, Safety stockÂ Â